Association between Level of Vitamin D with Environmental and Bioelement Factors in Children with Attention Deficit Hyperactivity Disorder (ADHD) - Gholamreza Noorazar; Gita Mehdizadeh; Aida Ghaffari; Nadia Dehbokri; Mohammad Taghi Khodayari; Saba Ghaffary (Tabriz University of Medical Sciences, 2018)
Background: Attention deficit hyperactivity disorder (ADHD) is a behavioral disorder. The exact pathophysiology of ADHD is not completely recognized. Previous studies have shown the role of different genetic and environmental factors in it. This study investigates the relationship between vitamin D and environmental factors in ADHD. Methods: In this study, 182 children from 2 to 18 years with confirmed ADHD were allocated in this cross-sectional study. Patients with a history of any chronic disease, anticonvulsants and corticosteroids consumption were excluded from the study. The ADHD severity was assessed by Conners' parent scale test. The level of serum vitamin D, ferritin, iron, total iron binding capacity, zinc, magnesium, calcium and routine complete blood count (CBC) were measured. Results: Although the results showed a U shaped pattern between vitamin D levels and ADHD severity, the correlation between vitamin D level did not show any significant relation with ADHD symptoms severity (p=0.786). Our data showed significant relation between level of vitamin D and ferritin in patients with ADHD (p=0.003). The analysis demonstrates significant relation between vitamin D level and duration of daily TV watching in children with ADHD (p=0.002). Conclusion: The vitamin D supplementation may improve ADHD symptoms in patients with vitamin D deficiency. In addition, due to the proved effect of ferritin level in ADHD and significant relation with vitamin D level in this study, treatment of vitamin D deficiency is necessary in children with ADHD. Replacing TV watching by more outdoor activity may improve ADHD symptoms.